A study of the seasonal presence of aphid species on the wheat crop (Ibaa 99) in the city of Baghdad (Journal of the College of Basic Education, 2022)
The results of this study were showed that there were four species of Aphids on the wheat crop(Ebaa99veriety) during the season,these are oat aphid Rhopalosiphumpadi (L.) ,corn aphidSchizaphisgraminum ,grain aphidR. maidis (Fitch) andEnglish grain aphidSitobionavenae (Fabricius) . Population densities of these species were varied, and the superiority was to R. padi at percentage of 86.56% of totalnumber of aphids species. While the corn aphid and grain aphids were 8.13% and 4.96% respectively. English grain aphid was appeared at low number at percentage of 0.35% for one weak at the end of seasonal and then disappeared. Temperatures and maturity of crop have impacted on the population density of aphid, it have been noticed that the low number of aphids was with temperaturesless than19°∁ and it was increased gradually with the increase of temperature . The higher density was 826 insect/50sample at temperatures between20-24℃ . Then it was decreased with an increase of temperatures up to 24℃ and higher until they reached to 15 insect/50sample. That is compatible with the maturity of crop.